Age-Related Changes in Children’s Associations of Economic Resources and Race - Elenbaas, Laura; Killen, Melanie (Frontiers in Psychology, 2016)
Age-related changes in children’s associations of economic resources and race were investigated. The sample (N = 308) included 5-6 year-olds (n = 153, M = 6.01 years, SD = .33 years) and 10-11 year-olds (n = 155, M = 11.12 years, SD = .59 years) of African-American (n = 93), European-American (n = 92), Latino (n = 62), Asian-American (n = 23), and multi-racial or multi-ethnic (n = 26) background. Participants matched pairs of target children (African-American and European-American) with visual indicators of low, middle, and high economic status. Children’s associations of economic resources with racial groups changed with age, and reflected different associations at high, middle, and low levels of the economic spectrum. Specifically, children associated targets of both races with middle economic status at a comparable rate, and, with age, increasingly associated targets of both races with indicators of middle economic status. By contrast, both younger and older children associated African-American targets with indicators of low economic status more frequently than European-American targets. Finally, children associated African-American targets with indicators of high economic status less frequently with age, resulting in a perceived disparity in favor of European-American targets at high economic status among older children that was not present among younger children. No differences were found by participants’ own racial or ethnic background. These results highlight the need to move beyond a dichotomized view (rich/poor) to include middle economic status when examining children’s associations of economic resources and race.